PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020) - Nensi Yuniarti Zs; Isma Nurangraini; Budi Astuti; Furqonti Ranidiah; Dinal Eka Pertiwi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine whether financial performance as measured by Non Performing Loans (NPL), Loan To Deposit Ratio (LDR), Capital Adequacy Ratio (CAR) has an effect on firm value and whether Corporate Social Responsibility (CSR) moderates the relationship between financial performance. to the value of the company. The study was conducted on banking companies listed on the Indonesian Stock Exchange in 2018-2020. This study uses the purposive sampling method, with the number of companies 12 x 3 years of research and a total sample of 36. The statistical method used is SPSS multiple linear regression, and Moderated Regression Analysis (MRA) with hypothesis testing, partial t statistical test, and coefficient of determination test. The results of this study state that: NPL has a positive and insignificant effect on firm value, with a significance of 0.128. LDR has a negative and significant effect on firm value, with a significance of 0.027. CAR has a positive and significant effect on firm value, with a significance of 0.007. with an adjusted r square value of 25.5%. Corporate Social Responsibility (CSR) cannot moderate the relationship between financial performance as measured by NPL and firm value. Corporate Social Responsibility (CSR) cannot moderate the relationship between financial performance as measured by LDR and firm value. Corporate Social Responsibility (CSR) cannot moderate the relationship between financial performance as measured by CAR and firm value.